CD83 acts as immediate early response gene in activated macrophages and exhibits specific intracellular trafficking properties - Langguth, Pia; Peckert, Katrin; Beck, Philipp; Kuhnt, Christine; Draßner, Christina; Deinzer, Andrea; Steinkasserer, Alexander; Wild, Andreas (Biochemical and Biophysical Research Communications, 2023)
Macrophages (MΦ) are remarkably plastic cells, which assume phenotypes in every shade between a pro-inflammatory classical activation, and anti-inflammatory or resolving activation. Therefore, elucidation of mechanisms involved in shaping MΦ plasticity and function is key to understand their role during immunological balance. The immune-modulating CD83 molecule is expressed on activated immune cells and various tissue resident MΦ, rendering it an interesting candidate for affecting MΦ biology. However, in-depth analyses of the precise kinetics and trafficking of CD83 within pro-inflammatory, LPS activated bone-marrow-derived MΦ have not been performed. In this study, we show that activation with LPS leads to a very fast and strong, but transient increase of CD83 expression on these cells. Its expression peaks within 2 h of stimulation and is thereby faster than the early activation antigen CD69. To trace the CD83 trafficking through MΦs, we employed multiple inhibitors, thereby revealing a de novo synthesis and transport of the protein to the cell surface followed by lysosomal degradation, all within 6 h. Moreover, we found a similar expression kinetic and trafficking in human monocyte derived MΦ. This places CD83 at a very early point of MΦ activation suggesting an important role in decisions regarding the subsequent cellular fate.
CRIS-Team Scopus Importer:2023-02-10
Keywords: CD83; expression; intracellular trafficking; lipopolysaccharide; macrophages

Soluble CD83 modulates human-monocyte-derived macrophages toward alternative phenotype, function, and metabolism. - Peckert-Maier, Katrin; Wild, Andreas; Sprißler, Laura; Fuchs, Maximilian; Beck, Philipp; Auger, Jean-Philippe; Sinner, Pia; Strack, Astrid; Mühl-Zürbes, Petra; Ramadan, Ntilek; Kunz, Meik; Krönke, Gerhard; et al. (Frontiers in Immunology, 2023)
Alterations in macrophage (Mφ) polarization, function, and metabolic signature can foster development of chronic diseases, such as autoimmunity or fibrotic tissue remodeling. Thus, identification of novel therapeutic agents that modulate human Mφ biology is crucial for treatment of such conditions. Herein, we demonstrate that the soluble CD83 (sCD83) protein induces pro-resolving features in human monocyte-derived Mφ biology. We show that sCD83 strikingly increases the expression of inhibitory molecules including ILT-2 (immunoglobulin-like transcript 2), ILT-4, ILT-5, and CD163, whereas activation markers, such as MHC-II and MSR-1, were significantly downregulated. This goes along with a decreased capacity to stimulate alloreactive T cells in mixed lymphocyte reaction (MLR) assays. Bulk RNA sequencing and pathway analyses revealed that sCD83 downregulates pathways associated with pro-inflammatory, classically activated Mφ (CAM) differentiation including HIF-1A, IL-6, and cytokine storm, whereas pathways related to alternative Mφ activation and liver X receptor were significantly induced. By using the LXR pathway antagonist GSK2033, we show that transcription of specific genes (e.g., PPARG, ABCA1, ABCG1, CD36) induced by sCD83 is dependent on LXR activation. In summary, we herein reveal for the first time mechanistic insights into the modulation of human Mφ biology by sCD83, which is a further crucial preclinical study for the establishment of sCD83 as a new therapeutical agent to treat inflammatory conditions.
EVALuna2:549687